Persepsi Masyarakat Terhadap Kegiatan Community Relations Dan Citra Lembaga STAIN Kediri - Prima Ayu Rizqi Mahanani (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2016)
Perception is an important aspect in communication activities, interaction, and relation among human. Perception contains values about something that is divided into good and bad values. Therefore, an institution needs to conduct good sensations to create positive interpretation about everything showed to other people. Community relations activities for an institution are expected be able to rise a perception that the institution is really a true relation for all stakeholders; hence, there is a dialogue with a group of community which form a good perception of college having integrity, and rise open relation, justice, and fortunate each other.This research purposes to know community perception in Dusun Laharpang, Puncu, Kediri in relation with the implementation of community relations activities conducted by the college students and lecturer. This study employed quantitative-descriptive research design through survey method with purposive sampling. The samples were 56 people. From the calculation of the mean, this reveals that the score is enough for the perception of Dusun Laharpang community to the community relations activities conducted by the college students and the lecturer of STAIN Kediri, and the perception of the community to STAIN Kediri institution.